2014
DOI: 10.7567/jjap.53.031001
|View full text |Cite
|
Sign up to set email alerts
|

N–H related defects in GaAsN grown through chemical beam epitaxy

Abstract: The local vibration modes of N–H related defects in GaAsN are studied using isotopes. When GaAsN is grown through chemical beam epitaxy (CBE) using triethylgallium/tris(dimethylamino)arsenic/monomethylhydrazine gas, there are several local vibration modes (LVMs) in Fourier transform infrared (FTIR) spectra. Signals with stretching mode peaks at 2952, 3098, and 3125 cm−1 are reported, along with new wagging and stretching mode peaks at 960 and 3011 cm−1, which exist only in crystals grown through CBE. When the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…When deuterated MMHy was used as the N source to grow GaAsN crystals, many N-D-related defects were generated in the grown film. 28) The peak at 940 cm −1 is the second-harmonic mode of N at the As site (N As ), and this defect is not related to the N-H structure. 29) Other peaks are attributed to LVMs of N-H-related defects, and the peaks at 960 cm −1 corresponds to the wagging mode and those at 2952 and 3098 cm −1 to the stretching modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When deuterated MMHy was used as the N source to grow GaAsN crystals, many N-D-related defects were generated in the grown film. 28) The peak at 940 cm −1 is the second-harmonic mode of N at the As site (N As ), and this defect is not related to the N-H structure. 29) Other peaks are attributed to LVMs of N-H-related defects, and the peaks at 960 cm −1 corresponds to the wagging mode and those at 2952 and 3098 cm −1 to the stretching modes.…”
Section: Introductionmentioning
confidence: 99%
“…29) Other peaks are attributed to LVMs of N-H-related defects, and the peaks at 960 cm −1 corresponds to the wagging mode and those at 2952 and 3098 cm −1 to the stretching modes. 28) This indicates that the N source MMHy plays an important role of supplying the H atoms in the N-H-related defects. However, the formation of these defects is strongly affected by both the growth methods and conditions, and the effects of arsenic (As) and gallium (Ga) source gases on the defect formation are yet unclear.…”
Section: Introductionmentioning
confidence: 99%
“…H atoms are strongly bound to N and different types of N-H complexes are generated [14,15]. Theoretical calculations suggest that one of the N−H defects plays the role of a double acceptor [16].…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the degradation is attributed to the high concentration of residual acceptors in unintentionally doped ptype films, which limits the depletion region width of the solar cell and decreases the photogenerated current [11][12][13]. N-H related complexes are the major defects in InGaAsN grown by chemical beam epitaxy (CBE), metal organic chemical vapor deposition (MOCVD), and molecular beam epitaxy (MBE) with H-irradiation [14][15][16][17][18]. Theoretical calculations suggested that one of the N-H defects plays the role of a double acceptor [19].…”
Section: Introductionmentioning
confidence: 99%